2018
DOI: 10.1016/j.celrep.2018.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Proton Sensitivity of Human GluN1-GluN2A NMDA Receptors

Abstract: Highlights d Cryo-EM structures of the human GluN1-GluN2A NMDA receptor resolved at pH 7.8 and pH 6.3 d The GluN2A-NTD adopts an open-and-twisted conformation in the agonist-bound state d Structures and modeling reveal that proton binding promotes closure of the GluN2A-NTD d Proton-induced NTD rearrangement is allosterically coupled to agonist-binding domains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 55 publications
3
45
1
Order By: Relevance
“…Potentiation of N1/N2B NMDA receptors by Mg or polyamines involves relief of tonic inhibition by protons (Traynelis et al, 1995;Paoletti et al, 1995;Mony et al, 2011). Recent structural analysis (Jalali-Yazdi et al, 2018;Regan et al, 2018;Zhang et al, 2018) confirms earlier evidence (Gielen et al, 2009;Yuan et al, 2009) that conformational changes in the ATD and LBD underlie proton inhibition. In addition, however, mutations in the SY-TANLAAF motif of both N1 and N2 subunits also can alter the potency of proton inhibition (Low et al, 2003), highlighting the mechanistic link between agonist binding and the bundlecrossing gate (Ladislav et al, 2018;Wilding and Huettner, 2019).…”
Section: Acidic Ph Reduces CD Activationsupporting
confidence: 59%
“…Potentiation of N1/N2B NMDA receptors by Mg or polyamines involves relief of tonic inhibition by protons (Traynelis et al, 1995;Paoletti et al, 1995;Mony et al, 2011). Recent structural analysis (Jalali-Yazdi et al, 2018;Regan et al, 2018;Zhang et al, 2018) confirms earlier evidence (Gielen et al, 2009;Yuan et al, 2009) that conformational changes in the ATD and LBD underlie proton inhibition. In addition, however, mutations in the SY-TANLAAF motif of both N1 and N2 subunits also can alter the potency of proton inhibition (Low et al, 2003), highlighting the mechanistic link between agonist binding and the bundlecrossing gate (Ladislav et al, 2018;Wilding and Huettner, 2019).…”
Section: Acidic Ph Reduces CD Activationsupporting
confidence: 59%
“…We have previously shown that these cells express NMDAR that mediates iCa 2+ rise through its release from IC pools, similar to findings from other groups, [8][9][10] along with mΔΨ depletion. Interestingly, given the relevance of pH for NMDAR channel function, [15][16][17] here we found that iCa 2+ rise is mainly elicited by acidic pH, rather than NMDA itself. However, and despite iCa 2+ responses were very similar between HBSS/pH6 and NMDA/ pH6, we unmasked that NMDA also activated cellular mechanisms that are evident only after a subsequent challenge with HBSS/pH6.…”
Section: Discussionmentioning
confidence: 55%
“…[11][12][13][14] Furthermore, the study of pH in NMDAR function is critical because it has been known for some time that the NMDAR is subject to proton inhibition because its proton sensor is tightly coupled with the ion channel gate, and the structural basis of this has been recently elucidated. [15][16][17] Moreover, the NMDA concentration used here has been found by us and others to regulate astrocyte and specific neuronal functions. 5,18,19 In our previous work, we also demonstrated that intracellular Ca 2+ (iCa 2+ ) rise was sensitive to competitive NMDAR inhibitors or GluN1 subunit Knock Down, demonstrating NMDAR involvement.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…GluN2A NTD is also responsible for receptor structural changes in a closed conformation due to extracellular protonation (i.e., pH variations), which were shown to be independent of plasma membrane potential [44][45][46] and agonist binding [47]. This event was shown to be synergistically promoted by other NMDAR inhibitors, such as Zn 2+ [48]. Recently, R370W and P79R mutations of the GRIN2A (Glutamate Ionotropic Receptor NMDA Type Subunit 2A) gene, encoding for the GluN2A subunit, have been associated with augmented and reduced sensitivity to Zn 2+ , respectively [49].…”
Section: Nmdar Structure: Focus On the Glun2a Subunitmentioning
confidence: 98%